2013
DOI: 10.1002/elsc.201200201
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotopes of methane for real‐time process monitoring in anaerobic digesters

Abstract: Efficient operation and stability of biogas plants requires continuous monitoring of the digester content. Traditional laboratory analysis of digester sludge is often complex and time-consuming and shows a delayed response to disruptions within the fermentation process. As a new approach, we applied an online measurement technique (laser absorption spectroscopy) for real-time monitoring of stable carbon isotopes of methane (δ 13 C CH 4 ) in a pilot-scale biogas digester (3500 L) regularly fed with maize silage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Reflecting the ammonia inhibition effects on methanogenesis based on traditional molecular biological methods is time consuming and costly, and thus difficult to apply as online measurement and assessment. Compound‐specific stable isotope analysis (CSIA) of the produced biogas, as an alternative to standard process parameters, has been suggested as a potential monitoring tool for the assessment of methanogenesis in AD since methanogenesis as the terminal metabolic pathway in AD is associated with a significant carbon stable isotope fractionation and can be characterized by hydrogen and carbon stable isotope ratios ( 2 H/ 1 H, 13 C/ 12 C). Recent developments in isotope analytical technologies allow the online monitoring of the carbon isotope composition of methane and carbon dioxide in laboratory‐scale and industrial‐scale biogas reactors , .…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting the ammonia inhibition effects on methanogenesis based on traditional molecular biological methods is time consuming and costly, and thus difficult to apply as online measurement and assessment. Compound‐specific stable isotope analysis (CSIA) of the produced biogas, as an alternative to standard process parameters, has been suggested as a potential monitoring tool for the assessment of methanogenesis in AD since methanogenesis as the terminal metabolic pathway in AD is associated with a significant carbon stable isotope fractionation and can be characterized by hydrogen and carbon stable isotope ratios ( 2 H/ 1 H, 13 C/ 12 C). Recent developments in isotope analytical technologies allow the online monitoring of the carbon isotope composition of methane and carbon dioxide in laboratory‐scale and industrial‐scale biogas reactors , .…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of microbial adaptation to environmental conditions is also very important to understand the complex interplay between bacteria and methanogens [ 15 , 16 ], particularly during acclimatization leading to successful and efficient reactor operation [ 17 ]. Moreover, correlations of methanogenic community data with process parameters have been reported to contain decisive information about shifting pathway dominance during biogas production [ 9 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is verified by the short-term fluctuations caused by daily feeding events. The characteristic depletion/enrichmentpattern correlation with feeding events which was also observed in experiments conducted at a semi-scale fermenter (Polag et al, 2013b) may be explained in several ways. Anaerobic digestion of organic matter is a multi-step process where physicochemical and biochemical reactions occur both sequentially and in parallel.…”
Section: Resultsmentioning
confidence: 85%
“…In that study the optical technique was suggested as a suitable online tool for biogas monitoring studies. A first application of this technique at a semi-scale biogas reactor (2500 L) at the Bavarian State Research Center for Agriculture showed promising results (Polag et al, 2013b).…”
Section: Introductionmentioning
confidence: 98%